Determinants of Islamic bank's leverage ratio in Malaysia / Noor Fadhzana Mohd Noor - Mohd Noor, Noor Fadhzana (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
This study examines the relationship between leverage ratio, bank’s performance, size and profit equalisation reserve. Using GMM estimators, both difference and system, we find significant relationship between current leverage ratio and previous leverage ratio and profit equalization reserve. Overall, our results are consistent with the several past literatures with addition of determining impact of profit equalization reserve on leverage ratios of Islamic banks in Malaysia.